A Case Report on Pantoprazole Induced VIT.B12 Deficiency - Pelluri, Ranakishore; Begum, Shaik Shafiya; Sowmya, Nallajerla; Jyothsna, Medarametla; Prathyusha, S.; Divya, Yedluri; Poornachand, Tadipudi; Reddy, Thirupathi Vivek; Jhansirani, Kakumanu; Umamounika, B.; Ramarao, Nadendla (Indian Journal of Pharmacy Practice)
A 40 yr old male patient suffering with GERD was initially prescribed with Pantoprazole 40 mg OD for 15 days. After the treatment, suddenly the patient started feeling uncharacterized dizziness and fatigue. The patient consulted his physician who is a gastroenterologist. After a thorough examination the physician asked the patient for blood tests which revealed that the Hb is normal but the amount of Vit.B12 present in the blood is less than the normal. It was confirmed that, after the use of Pantoprazole, Vit.B12 blood levels have decreased which lead to the symptoms. This case report summarizes that on long term use of pantoprazole should be supported by supplemental therapy with Vit.B12. Background: Proton pump inhibitors (PPI) are now one of the most widely used classes of drugs. PPIs have proven to have a very favourable safety profile and it is unusual for a patient to stop these drugs because of side effects. However, increasing numbers of patients are chronically taking PPIs for gastroesophageal reflux disease and a number of other common persistent conditions, therefore the long-term potential adverse effects are receiving increasing attention. One area that is receiving much attention and generally has been poorly studied is the long-term effects of chronic acid suppression on the absorption of vitamins and nutrients.
Keywords: Pantoprazole; Gastroesophagal reflux disease; Gastric ulcer; Vitamin B12 Deficiency; Dizziness